Instagram: is it a Social Media Solution to Promote Sustainable Tourism? - Aprih Santoso; Vensy Vydia; Ardiani Ika sulistyawati (Universitas Dharma Wacana, 2022)
There is a tourism promotion business phenomenon that is carried out through social media Instagram in the city of Semarang. This phenomenon shows the current realization of tourism promotion activities through Instagram social media, with the aim of research to examine tourism promotion through Instagram social media carried out in Semarang City. This study uses qualitative research with a case study approach by taking tourism research objects in the city of Semarang. Data collection in this study was obtained through interviews, observations, documentation with informants, namely Instagram account admins, Instagram social media users, academics in the tourism sector, and travel agencies that use Instagram social media as a promotional media. The results of the analysis of tourism promotion in Semarang City through Instagram social media are carried out in stages, namely: content creation, platform determination, program planning, program implementation, and monitoring & evaluation. Analysis of the advantages of promotion through Instagram social media, namely promotional media that is not paid, can be used at any time, is easy to use, can be connected to other social media, and has many users. Analysis of the weakness of promotion through Instagram social media is that it must be updated regularly, the authenticity of the product is still in doubt, prone to spamming. Furthermore, the analysis of sharia tourism promotion through Instagram social media has very effective prospects for the future.